Land use and Europe’s renewable energy transition: identifying low-conflict areas for wind and solar development - Kiesecker, Joseph M.; Evans, Jeffrey S.; Oakleaf, James R.; Dropuljić, Kasandra Zorica; Vejnović, Igor; Rosslowe, Chris; Cremona, Elisabeth; Bhattacharjee, Aishwarya L.; Nagaraju, Shivaprakash K.; Ortiz, Anthony; Robinson, Caleb; Ferres, Juan Lavista; et al. (Frontiers in Environmental Science, 2024)
Continued dependence on imported fossil fuels is rapidly becoming unsustainable in the face of the twin challenges of global climate change and energy security demands in Europe. Here we present scenarios in line with REPowerEU package to identify Renewables Acceleration Areas, that support rapid renewable expansion, while ensuring minimal harm to places important for biodiversity and rural communities. We calculated the area needed to meet renewable energy objectives under Business-as-Usual (BAU) and Low-conflict (LCON) development scenarios within each country, providing a broad overview of the potential for renewable energy generation to reduce impacts when development is steered toward lower conflict lands. Our analysis shows that meeting renewable energy objectives would require a network of land-based wind turbines and solar arrays that would requireencompassing upwards of 164,789 km 2 by 2030 and 445,654 km 2 by 2050, the latter roughly equivalent to the land an area roughly the size of the country of Sweden. Our results highlight that BAU development patterns disproportionately targets high-conflict land cover types. By 2030, depending on the development pathway, solar and wind development are projected to impact approximately 4,386 -20,996 km2 and 65,735 -138,454 km2 of natural and agricultural lands, respectively.and depending on the development pathway, will impact approximately 4,386-20,996 km 2 of natural and agricultural lands for solar development and approximately 65,735-138,454 km 2 for wind development by 2030. As renewable energy objectives increase from 2030 to 2050 impacts to natural and agricultural lands also increase concomitantly, with upwards of 33,911km 2 from future solar development and 399,879 km 2 from wind development. Despite this large footprint, low-conflict lands can generate substantial renewable energy: 6.6 million GWh of solar and 3.5 million GWh of wind, 8-31 times 2030 solar objectives and 3-5 times 2030 wind objectives.Top-emitting countries that have large renewable energy objectives (Germany, Italy, Poland, France, Spain) and countries that lack flexibility in how to meet objectives on low-conflict lands alone, (like Albania,